Globalization, Financial Development and Economic Growth - Altug Kazar; Gorkemli Kazar (International Journal of Economics and Financial Issues, 2016)
Widespread globalization and integration remove the borders but this leads to an increase in the income differences among countries. Today, the evaluation process of economic growth experience of countries shows that globalization degree of the economy is also important as the financial development. This paper investigates the relationship between financial development, globalization and economic growth for the case of the countries classified according to income levels over the period 1980–2010. After considering the panel characteristics of the dataset, long-run relationships among financial development, economic growth and the other key growth factors are analyzed by dynamic ordinary least squares (DOLS)  method. The empirical results suggest that the effective policy applications are different according to the country classifications. Keywords: Economic Growth, Globalization, Financial Development, Dynamic Ordinary Least Squares